1996
DOI: 10.1097/00000539-199610000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Aprotinin Reduces Interleukin-8 Production and Lung Neutrophil Accumulation After Cardiopulmonary Bypass

Abstract: Pulmonary neutrophil entrapment and resultant oxidative injury is thought to be the primary mechanism of cardiopulmonary bypass (CPB) induced lung injury. Interleukin-8 (IL-8), a potent neutrophil chemoattractant induced by cytokines, including tumor necrosis factor-alpha (TNF), is found in increased concentrations in bronchial alveolar lavage fluid (BALF) in lung inflammation. Since aprotinin reduces TNF release during CPB, the effects of aprotinin on BALF IL-8 concentrations and neutrophil levels were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 19 publications
1
19
0
1
Order By: Relevance
“…1 Important features of these inflammatory reactions include the activation of complement 2 and leukocytes, 1 the release of proinflammatory cytokines, 3 alterations in nitric oxide metabolism, 4 and increased production of oxygen free radicals, which in some cases leads to oxidant stress injury. 5,6 Among the strategies used to reduce the inflammatory reactions induced by CPB and its consequences are treatment with steroids, 7 aprotinin, 8,9 heparin-coated CPB circuits, 10 and hemofiltration. 11 The omission of CPB itself might be a more radical and effective way of counteracting the effects of these inflammatory reactions and oxidative stress.…”
mentioning
confidence: 99%
“…1 Important features of these inflammatory reactions include the activation of complement 2 and leukocytes, 1 the release of proinflammatory cytokines, 3 alterations in nitric oxide metabolism, 4 and increased production of oxygen free radicals, which in some cases leads to oxidant stress injury. 5,6 Among the strategies used to reduce the inflammatory reactions induced by CPB and its consequences are treatment with steroids, 7 aprotinin, 8,9 heparin-coated CPB circuits, 10 and hemofiltration. 11 The omission of CPB itself might be a more radical and effective way of counteracting the effects of these inflammatory reactions and oxidative stress.…”
mentioning
confidence: 99%
“…Many, but not all, studies in CPB-supported cardiac surgery have provided evidence for an anti-inflammatory action of aprotinin. [11][12][13][14][15][16][17][18][19][35][36][37] There seems to be conflicting evidence as to the presumed anti-inflammatory actions of aprotinin. On a theoretical basis and largely confirmed by in vitro investigations, aprotinin has potential antiinflammatory actions.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Aprotinin has been demonstrated to reduce inflammation in CPB-supported cardiac surgery. [11][12][13][14][15][16][17][18][19] Whether aprotinin can further reduce inflammation in off-pump coronary artery bypass graft (OPCAB) surgery has currently not been investigated. In addition, aprotinin has been reported to have cardioprotective properties during cardiac surgery with CPB by reducing ischemia-reperfusion injury, including reduced cardiac troponin I (cTnI) release in coronary artery bypass graft (CABG) patients.…”
Section: B Oth Mechanical Injury During Cardiac Surgerymentioning
confidence: 99%
“…Besides its well-known protective effects on platelets and its antifibrinolytic actions, some anti-inflammatory properties have been recently attributed to aprotinin, and this ability has been shown to be dose-dependent in a variety of in vitro systems [45, 46]. This suggested that actions of aprotinin include the prevention of upregulation of neutrophil CD11b integrin necessary for neutrophil adherence and degranulation, suppression of the plasma increases of the proinflammatory cytokines IL-6 and IL-8 and enhancement of the release of the anti-inflammatory cytokine IL-10 [47, 48]. Moreover, aprotinin has been shown in vitro to inhibit TNF secretion from activated macrophages by 51% and to reduce elastase release from neutrophils [49, 50].…”
Section: Discussionmentioning
confidence: 99%